Dynamic on Demand Scaling and Load Balancing: Enhancing Application Performance and Usability through Load Balancing in Cloud Computing (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cloud computing is a well-defined computing paradigm in which data and assets are collected from cloud service providers over the Internet using well-designed Internet-based devices and software. Cloud computing is a collection of computing resources and services that make it available to customers at low cost. Sharing resources can lead to a stalemate due to lack of such resources. The process of distributing network traffic to different servers is called load balancing. As a result, a single server will not be overloaded. Load balancing improves application responsiveness by evenly distributing jobs. It also improves the usability of programs and websites. The purpose of this document is to help you better understand load balancing.